Perbedaan Teknik Penggorengan Terhadap Kadar Protein Terlarut Dan Daya Terima Abon Jamur Tiram (Pleurotus Ostreatus) - Adawiyah, Mis Rabiatul; , Rusdia Rauf, S.TP., MP (2016)
Introduction: Shredded mushroom is fast food made from oyster mushrooms and processed by frying with deep frying and pan frying. The impact of the frying is the changing nature of the protein. Protein is easily damaged when processed using high temperatures. Purpose: The purpose of this study was to determine differences in the frying technique on levels of soluble protein and acceptability shredded oyster mushrooms. Methods: The study design used was completely randomized design with 2 frying technique is deep frying at 180 °C with a time of 15 minutes and pan frying at 120 °C with a time of 45 minutes. Data analysis of soluble proteins and acceptance shredded oyster mushrooms were analyzed using T-Test Indepedent with a confidence level of 95%. Results: The highest levels of soluble protein in the shredded mushrooms is using deep frying technique is 1.05%, while the lowest levels of soluble protein in shredded oyster mushrooms using pan frying technique is 0.80%. Receptivityof color deep frying is higher than the receptivity of color pan frying. Conclusion: There is a difference frying technique on levels of soluble protein shredded oyster mushrooms. There are differences in the frying technique against the receptivity of color shredded oyster mushrooms. Suggestion: it is advisable to use deep frying technique because a frying technique most preferred by panelist.